Organizational Motivations for Adopting CMMI-based Software Process Improvement: An Extended and Updated Systematic Review - Plácido, Luiz Sérgio; Araújo, Leonardo; Sampaio, Suzana; Marinho, Marcelo; Godoi, Robson; Luna, Alexandre; da Silva, Fabio Q. B. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2012)
In this paper, we described an update and extension of a systematic review about organizational motivations for adopting CMMI-based Software Process Improvement (SPI). We applied the systematic review method to search, select, evaluate, and synthesize the published research related to this topic. We then compared our findings to those of another systematic review previously published. Our findings showed that the motivations to engaged on CMMI- based SPI changed from being related to software quality to focusing on complying with customers’ requirements and satisfaction, as well to conquer external validation.